2022
DOI: 10.1177/13591053221111850
|View full text |Cite
|
Sign up to set email alerts
|

Moral distress during COVID-19: The importance of perceived organizational support for hospital nurses

Abstract: Moral distress, or the inability to act congruent with moral beliefs, has been of concern for healthcare professionals especially since the COVID-19 pandemic. Hospital nurses are particularly affected in their roles with mounting administrative pressures and demands. We examined whether general and COVID-specific support in employing healthcare organizations predicted moral distress in a sample of inpatient hospital nurses. A total of 248 nurses completed the Measure of Moral Distress for Healthcare Profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Our results showed that HCWs reported increased prospects of leaving their jobs due to the experience and impacts of moral stressors, an outcome that is consistent with the findings of others using the same measure in ICUs (Petrisor et al, 2021 ; Silverman et al, 2022 ), neonatal ICUs (Hally et al, 2021 ), and with nurses more generally (Sheppard et al, 2022 ). Using categorisations provided by Epstein et al ( 2019 ) to classify moral stressors, four out of the five most frequently endorsed situations were classified as originating at the organizational level, which is consistent with findings from smaller-scale studies of HCWs during the COVID-19 pandemic (Latimer et al, 2022 ; Petrisor et al, 2021 ). Stressors that fell into both the high-frequency and high-distress categories included those involving patient care requirements that exceeded the capacity that HCWs felt comfortable managing, a perceived lack of resource availability, and a belief that healthcare administrators were not adequately addressing issues that had the potential to compromise the quality of patient care.…”
Section: Discussionsupporting
confidence: 71%
“…Our results showed that HCWs reported increased prospects of leaving their jobs due to the experience and impacts of moral stressors, an outcome that is consistent with the findings of others using the same measure in ICUs (Petrisor et al, 2021 ; Silverman et al, 2022 ), neonatal ICUs (Hally et al, 2021 ), and with nurses more generally (Sheppard et al, 2022 ). Using categorisations provided by Epstein et al ( 2019 ) to classify moral stressors, four out of the five most frequently endorsed situations were classified as originating at the organizational level, which is consistent with findings from smaller-scale studies of HCWs during the COVID-19 pandemic (Latimer et al, 2022 ; Petrisor et al, 2021 ). Stressors that fell into both the high-frequency and high-distress categories included those involving patient care requirements that exceeded the capacity that HCWs felt comfortable managing, a perceived lack of resource availability, and a belief that healthcare administrators were not adequately addressing issues that had the potential to compromise the quality of patient care.…”
Section: Discussionsupporting
confidence: 71%
“…The majority of studies were carried out in Iran (n = 13) 2 20,21,22,23,24,25,26,27,28,29,30,31,32 and the US (n = 10). [33][34][35][36][37][38][39][40][41][42] Several studies were carried out in Asia (n = 11) 10,[43][44][45][46][47][48][49][50][51] and Europe (n = 6). [52][53][54][55][56][57] One study was carried out in Australia, 4 Canada 58 and Egypt, 7 respectively.…”
Section: Hospital Ethical Climatementioning
confidence: 99%
“…These aspects are thus assumed to contribute to a more positive ethical climate. This alternative, more general, perspective on ethical climates also came along with aligning ethical climates more closely with peculiarities of certain industries and professions (Brinkmann, 2002;Brinkmann & Henriksen, 2008), like healthcare, services, and accounting (e.g., Friend et al, 2020;Latimer et al, 2023), or like nurses, real estate agents, and sales agents (e.g., Brinkmann, 2009;Kadic-Maglajlic et al, 2019). In some of these focus areas, this has even led to adapting the measurement instruments to the specific contexts as in healthcare, where a widely used assessment tool is the Hospital Ethical Climate Scale (Olson, 1998).…”
Section: Ethical Climates and Their Outcomesmentioning
confidence: 99%
“…This level builds on the idea of specific professional ethics and transcends country and organizational levels (Brinkmann, 2002). The explanatory potential this vocational level holds for the study on ethical climates has been recognized only to a small extent yet and has predominantly materialized in conceptual developments aiming to explain the nature and outcomes of ethical climates in a specific profession like marketing, healthcare, and financial industries (Brinkmann, 2002(Brinkmann, , 2009 or a specific profession like sales agents or nurses (Bush et al, 2017;Kadic-Maglajlic et al, 2019;Latimer et al, 2023;Olson, 1998). Still, this perspective has drawn predominantly on peculiarities of one specific focal industry or profession and relationships of ethical climates to outcomes in such a more focused context.…”
Section: Theoretical Implications and Future Researchmentioning
confidence: 99%